Business models for Serious Games developers - transition from a product centric to a service centric approach. - Jannicke Baalsrud Hauge; Stefan Wiesner; Rosa Garcia Sanchez; Poul Kyvsgaard Hansen; Giusy Fiucci; Michel Rudnianski; Jon Arambarri Basanez (Serious Games Society, 2014)
In the context of the serious games industry, up to now the most commonly used BM among developers representing SMEs consists in offering an individual product to the customer, based on tailored one-of a kind production. Such production has high costs and low re-usability and leads to a long time-to-market. For an industry dealing with products highly dependent on technological advances, this implies high risks for failure and thus being put out of business. Consequently, an increasing number of Serious Games developers are struggling to survive. These trends are not specific for the SG development sector, but can actually be observed in several others, like software industry as well as the manufacturing industry, where a transition to less product-oriented BM can be observed. This article is based on an analysis of cases studies to outline how such a transition might be possible also within serious game industry, but also to discuss the threats and opportunities of the transition, both based on case studies as well as on comparison with experiences in other industries